Stem Cell Research and Therapeutics - Shi, Yanhong; Clegg, Dennis O.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
This book is an updated reference for one of the most exciting fields of biomedical research- Stem Cell Research and its therapeutic applications. Stem cell research holds great promise for the treatment of many human diseases that currently lack effective therapies. The set of chapters in this book provide insights into both basic stem cell biology and clinical applications of stem cell-based cell replacement therapies for a variety of human diseases, including cardiovascular diseases, neurological disorders, and liver degeneration. It also covers novel technologies for the culture and differentiation of both human embryonic stem cells and adult tissue stem cells. This book summarizes our current state of knowledge in stem cell research and integrates basic stem cell biology with regenerative medicine in an overall context. It is an essential reference for students, research fellows, academic and industrial scientists, and clinicians.
Retinal Pigment Epithelial Cells: Development In Vivo and Derivation from Human Embryonic Stem Cells In Vitro for Treatment of Age-Related Macular Degeneration -- Progenitor Cell Transplantation for Retinal Disease -- Negative Regulation of Endogenous Stem Cells in Sensory Neuroepithelia: Implications for Neurotherapeutics -- Epigenetic Control of Neural Stem Cell Self-Renewal and Specification -- Neural Stem Cells and Neurogenic Niche in the Adult Brain -- Progressing Neural Stem Cell Lines to the Clinic -- Human Neural Stem Cells for Biopharmaceutical Applications -- The Analysis of MicroRNAs in Stem Cells -- Optimized Growth of Human Embryonic Stem Cells -- Potential of Stem Cells in Liver Regeneration -- Cell Transplantation Therapy for Myocardial Repair: Current Status and Future Challenges -- Surgical Stem Cell Therapy for the Treatment of Heart Failure -- Use of Combinatorial Screening to Discover Protocols That Effectively Direct the Differentiation of Stem Cells -- Adult Stem Cell Therapies for Tissue Regeneration: Ex Vivo Expansion in an Automated System -- The Hair Follicle Stem Cell as the Paradigm Multipotent Adult Stem Cell.
Keywords: Medicine; Cancer research; Oncology; Biomedicine; Cancer Research; Oncology; Electronic books